Feasibility and Diagnostic Performance of Voxelwise Computed Diffusion‐Weighted Imaging in Breast Cancer. Issue 6 (16th October 2018) - Zhou, Jiejie; Chen, Endong; Xu, Huazhi; Ye, Qiong; Li, Jiance; Ye, Shuxin; Cheng, Qinyuan; Zhao, Liang; Su, Min‐ying; Wang, Meihao
Abstract : Background: Conventional diffusion‐weighted imaging (DWI) with high b‐values may improve lesion conspicuity, but with a low signal intensity and thus a low signal‐to‐noise ratio (SNR). The voxelwise computed DWI (vcDWI) may generate high‐quality images with a strong lesion signal and low background. Purpose: To evaluate the feasibility and diagnostic performance of vcDWI. Study Type: Retrospective. Population: In all, 67 patients with 72 lesions, 33 malignant and 39 benign. Field Strength/Sequence: 3T, including T2 /T1, DWI with two b‐values, and dynamic contrast‐enhanced MRI (DCE‐MRI). Assessment: Computed DWI (cDWI) with high b‐values of 1500, 2000, 2500 s/mm 2 (cDWI1500, cDWI2000, cDWI2500 ) and vcDWI were generated from measured DWI (mDWI). The mDWI, cDWIs and vcDWI were evaluated by three readers independently to determine lesion conspicuity, background signal suppression, overall image quality using 1–5 rating scales, as well as to give BI‐RADS scores. The mean apparent diffusion coefficient (ADC) value for each lesion was measured. Statistical Tests: Agreement among the three readers was evaluated by the intraclass correlation coefficient. Receiver operating characteristic (ROC) analysis was performed to compare the diagnostic performance based on reading of mDWI, cDWIs, vcDWI, and the measured ADC values. Results: vcDWI provided the best lesion conspicuity compared with mDWI and cDWIs ( P  < 0.005). For overall image quality, vcDWI was significantly better than cDWI ( P  < 0.005), but not significantly better compared with mDWI for two readers ( P  = 0.037 and P  = 0.013) and significantly worse for the third reader ( P  < 0.005). Background signal suppression was the best on cDWI2500, and better on vcDWI than on mDWI, cDWI1500, and cDWI2000 . The AUC value for differential diagnosis was 0.868 for mDWI, 0.862 for cDWI1500, 0.781 for cDWI2000, 0.704 for cDWI2500, 0.946 for vcDWI, 0.704 for ADC value, and 0.961 for DCE‐MRI. Data Conclusion: vcDWI was implemented without increasing scanning time, and it provided excellent lesion conspicuity for detection of breast lesions and assisted in differentiating malignant from benign breast lesions. Level of Evidence : 4 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2018.